Finance and Development, March 1976. (Finance and Development; Finance and Development ;, 1976)
This paper highlights that agreement on an important package of reforms of vital significance to the future of the international monetary system was reached at a meeting of the Interim Committee of the Board of Governors of the IMF on the International Monetary System in Kingston, Jamaica, on January 7-8, 1976. The reforms include a substantial quota increase for almost all members, as well as an increase in access to the IMF's resources for all member countries in the period prior to implementation of the increase in their IMF quotas, and some other amendments.